INVENTORY AND POPULATION STUDY OF FUNGI FROM THE RIVERINE DRINKING WATER - K. CHRISTAL THANGA PADMINI; B. CHRISTUDHAS WILLIAMS; M. MURUGAN (International Journal of Pharma and Bio Sciences, 2013)
The present work was carried out on studying the impact on diversity of aquatic fungi to assess the water quality. Tamiraparani river water was assessed at Kuzhithurai study stations in the study month of September, 2012, With reference to aquatic fungal diversity. During the study, 12 aquatic fungal species fungal species belonging to Aspergillus sp., Fusarium sp., Penicillum sp., were isolated and identified. Maximum percentage of fungal species identified is Aspergillus sp., and the lowest is Sporothrix sp., and Phialophora sp.,. The present investigation revealed that the difference in the percent of occurrence, distribution of aquatic fungi in Tamiraparani river.